Analysis of Social Media Behavior in Banking Institutions using Text Mining - D. , Hemavathi; H. , Srimathi (International Journal of Psychosocial Rehabilitation, 2020)
Social networks are the foremost vital communication channels in recent years that are well-liked among the various social teams. These networks affected the ideas and policies of people, teams, and communities. Every day, a lot of tweets on Twitter are being revealed. These tweets mirror the opinions and beliefs of their publishers and have an effect on others in addition. Therefore, it’s vital to investigate these tweets and establish and classify trends of various users. A set of options has been extracted to portray every cluster exploiting various text mining strategies and store these characteristics within the info. Text mining, sentiment analysis, and opinion mining techniques are wont to accomplish this extraction. During this paper, the important tweets were fetched on banking establishments. Later, the fetched tweets were applied to many steps to investigate the social media behavior by using text mining.